BART Inhibits Pancreatic Cancer Cell Invasion by Rac1 Inactivation through Direct Binding to Active Rac1 - Keisuke Taniuchi; Kunihiko Yokotani; Toshiji Saibara (Neoplasia: An International Journal for Oncology Research, 2012)
We report that Binder of Arl Two (BART) plays a role in inhibiting cell invasion by regulating the activity of the Rho small guanosine triphosphatase protein Rac1 in pancreatic cancer cells. BART was originally identified as a binding partner of ADP-ribosylation factor-like 2, a small G protein implicated as a regulator of microtubule dynamics and folding. BART interacts with active forms of Rac1, and the BART-Rac1 complex localizes at the leading edges of migrating cancer cells. Suppression of BART increases active Rac1, thereby increasing cell invasion. Treatment of pancreatic cancer cells in which BART is stably knocked down with a Rac1 inhibitor decreases invasiveness. Thus, BART-dependent inhibition of cell invasion is likely associated with decreased active Rac1. Suppression of BART induces membrane ruffling and lamellipodial protrusion and increases peripheral actin structures in membrane ruffles at the edges of lamellipodia. The Rac1 inhibitor inhibits the lamellipodia formation that is stimulated by suppression of BART. Our results imply that BART regulates actin-cytoskeleton rearrangements at membrane ruffles through modulation of the activity of Rac1, which, in turn, inhibits pancreatic cancer cell invasion.